A large eddy simulation of the dispersion of traffic emissions by moving vehicles at an intersection. (15th October 2019) - Woodward, Huw; Stettler, Marc; Pavlidis, Dimitrios; Aristodemou, Elsa; ApSimon, Helen; Pain, Christopher
Abstract: Traffic induced flow within urban areas can have a significant effect on pollution dispersion, particularly for traffic emissions. Traffic movement results in increased turbulence within the street and the dispersion of pollutants by vehicles as they move through the street. In order to accurately model urban air quality and perform meaningful exposure analysis at the microscale, these effects cannot be ignored. In this paper we introduce a method to simulate traffic induced dispersion at high resolution. The computational fluid dynamics software, Fluidity, is used to model the moving vehicles through a domain consisting of an idealised intersection. A multi-fluid method is used where vehicles are represented as a second fluid which displaces the air as it moves through the domain. The vehicle model is coupled with an instantaneous emissions model which calculates the emission rate of each vehicle at each time step. A comparison is made with a second Fluidity model which simulates the traffic emissions as a line source and does not include moving vehicles. The method is used to demonstrate how moving vehicles can have a significant effect on street level concentration fields and how large vehicles such as buses can also cause acute high concentration events at the roadside which can contribute significantly to overall exposure. Highlights: Novel method for simulating traffic induced dispersion at the microscale. Vehicles modelled as a second fluid coupled with an instantaneous emissions model. Vehicles dominate dispersion for low wind speed test case. Large vehicles cause very short, acute exposure events at roadside. Acute exposure events at roadside can contribute significantly to overall exposure.